Analysis of Digital Marketing Utilization: Prospects for Implementing Artificial Intelligence-Based Chatbots in Madura Snack Micro, Small, and Medium Enterprises (MSMEs) - Firdaus, Jannatul; Arifah, Hertin Khalifatun Nisa; Noviantari, Tantri (SAFE-Network, 2025)
The use of digital technology, particularly AI (Artificial Intelligence)-based chatbots, has great potential to improve efficiency and customer experience for Micro, Small, and Medium Enterprises (MSMEs). However, the implementation of this technology in MSMEs, especially in Madura specialty snack MSMEs, still faces various challenges. This study uses a qualitative approach with case studies to analyze the use of digital marketing with the prospect of implementing AI-based chatbots in Madura specialty snack MSMEs. Data was collected through interviews, observations, and documentation, then analyzed using NVivo 15 software. The results of the analysis show that although chatbots are already in use, their use is still considered limited by certain parties. The main benefits felt are work efficiency and quick responses. However, there are several major obstacles that hinder optimization, such as the limited understanding of MSME players, technical issues related to accuracy and language, as well as concerns about costs and resistance to change due to fear of losing personal interaction. Nevertheless, expectations for chatbot development vary, with business owners focusing on system integration, while consumers and employees expect product recommendation features. This study concludes that to optimize the use of this technology, continuous education and the availability of affordable chatbot solutions are needed.